2003
DOI: 10.1111/j.1559-1816.2003.tb02078.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Source Credibility and Message Framing on Exercise Intentions, Behaviors, and Attitudes: An Integration of the Elaboration Likelihood Model and Prospect Theory1

Abstract: This study examined the influence of source credibility and message framing on promoting physical exercise in university students. Participants were randomly assigned to reading a positively or negatively framed communication that was attributed to either a credible or a noncredible source. Exercise intentions and attitudes were measured immediately following the delivery of the communication and following a 2‐week delay. Exercise behavior was also measured following the delay. There were Source Frame interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
257
2
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(281 citation statements)
references
References 35 publications
14
257
2
8
Order By: Relevance
“…However the integration of regulatory focus theory into the standard method has utility and may explain null findings in research from the physical activity and health communication domain. For example, two investigations comparing the effectiveness of messages emphasizing benefits of physical activity versus costs of inactivity reported null findings at the 2-week follow-up (Jones, Sinclair, & Courneya, 2003;Jones, Sinclair, Rhodes, & Courneya, 2004). Results from the current study suggest that any message effect, and in particular the messages emphasizing benefits (i.e., promotion-focused messages), may have been suppressed as a result of individual differences in regulatory focus.…”
Section: Discussionmentioning
confidence: 54%
“…However the integration of regulatory focus theory into the standard method has utility and may explain null findings in research from the physical activity and health communication domain. For example, two investigations comparing the effectiveness of messages emphasizing benefits of physical activity versus costs of inactivity reported null findings at the 2-week follow-up (Jones, Sinclair, & Courneya, 2003;Jones, Sinclair, Rhodes, & Courneya, 2004). Results from the current study suggest that any message effect, and in particular the messages emphasizing benefits (i.e., promotion-focused messages), may have been suppressed as a result of individual differences in regulatory focus.…”
Section: Discussionmentioning
confidence: 54%
“…In line with Kahneman and Tversky's 7,8 conclusion that people show risk aversion under gain framings and risk-seeking behaviors under loss framings, several authors 2,4,6,11,[13][14][15] suggested that gain frames might be more effective in promoting disease prevention behaviors, whereas loss frames might be more effective for disease detection behaviors. In line with this hypothesis, gain frames have been more effective when promoting exercise, 16 reduced alcohol use, 17 parental use of children's car seat restraints, 18,19 skin cancer prevention behaviors, 20,21 and use of condoms to prevent HIV 22 ; loss frames have been more effective at encouraging individuals to engage in breast self-examination, 23,24 mammography screenings, [25][26][27][28][29][30] blood-cholesterol screenings, 31 HIV screenings, 32,33 and skin cancer detection. 20,34 Finally, for decisions about surgical procedures and treatments, gain frames (probability of success or survival) induce greater compliance than loss frames (probability of failure or death 10,[35][36][37][38] ).…”
Section: Introductionmentioning
confidence: 50%
“…For example, exercise promotion messages presented by a noncredible source resulted in little further consideration of the message, therefore limiting the potential influence of the message (Jones, Sinclair, & Courneya, 2003). Other researchers found that a highly credible source of exercise information (the American Heart Association) positively influenced attitudes and intentions toward exercise behavior (Arora, Stoner, & Arora, 2006).…”
Section: Source Credibilitymentioning
confidence: 99%